Gambaran Korban Dalam Menghadapi Kekerasan Dalam Rumah Tangga - Tobri, Farida Hayati; Widinarsih, Dini (Jurnal Ilmu Kesejahteraan Sosial, 2008)
Domestic violence is a social problem which has multiple causes and complex This research has founds that there are variety of domestic violence backgrounds, the intent of violence, the form of domestic violence, the impact of violence for women, and also the effort to ends domestic violence